Concurrent radiochemotherapy in advanced hypopharyngeal cancer - Krstevska, Valentina (BioMed Central, 2010)
BACKGROUND: Concurrent platinum-based radiochemotherapy has been recommended as a standard of care in patients with locally advanced squamous cell head and neck carcinomas. Unfortunately, there is a lack of level one evidence on best treatment approach for advanced hypopharyngeal cancer. This report aims to summarize the results of our study on concurrent radiochemotherapy in patients with advanced hypopharyngeal cancer. METHODS: A retrospective analysis of 41 patients with stage III-IV hypopharyngeal cancer was performed. All patients were treated with three dimensional conformal radiotherapy and received 70 Gy in 35 fractions (2 Gy per fraction, 5 fractions per week). In dependence of the period when radiotherapy was realized, two different treatment techniques were used. Concurrent chemotherapy consisted of cisplatin 30 mg/m(2 )given on a weekly basis. RESULTS: The median age was 52 years (range 29-70). Stage IV disease was recognized in 73.2% of the patients. Complete response rates at the primary site and at the metastatic neck lymph nodes were 68.3% and 36.6%, respectively. A complete composite response was present in 27 patients (65.9%). Median follow-up was 13 months (range 7-36). Distant metastases as initial failure occurred in 7 patients (46.7%). The 2-year local relapse-free survival and regional relapse-free survival rates were 55.2% and 75.8%, respectively. The 2-year locoregional relapse-free survival rate was 51.3%. The 2-year disease-free survival and overall survival rates were 29.3% and 32.8%, respectively. Confluent mucositis was developed in 46.3% of patients. Leucopenia grade 1 was the most frequent hematological toxicity. The median weight loss at the end of treatment was 12% (range 5-21). The worst grade of late toxicity was most commonly pronounced in the skin and in the subcutaneous tissue. CONCLUSIONS: Based on unsatisfactory results in our study we suggest that the use of sequential radiochemotherapy or chemotherapy given concomitantly with altered fractionation radiotherapy with the implementation of intensity-modulated radiotherapy as radiotherapy technique could represent treatment approaches able to improve outcome in patients with advanced hypopharyngeal cancer.